CAIX-Mediated Control of LIN28/let-7 Axis Contributes to Metabolic Adaptation of Breast Cancer Cells to Hypoxia - Gibadulinova, Adriana; Bullova, Petra; Strnad, Hynek; Pohlodek, Kamil; Jurkovicova, Dana; Takacova, Martina; Pastorekova, Silvia; Svastova, Eliska (International journal of molecular sciences, 2020)
Solid tumors, including breast cancer, are characterized by the hypoxic microenvironment, extracellular acidosis, and chemoresistance. Hypoxia marker, carbonic anhydrase IX (CAIX), is a pH regulator providing a selective survival advantage to cancer cells through intracellular neutralization while facilitating tumor invasion by extracellular acidification. The expression of CAIX in breast cancer patients is associated with poor prognosis and metastases. Importantly, CAIX-positive hypoxic tumor regions are enriched in cancer stem cells (CSCs). Here we investigated the biological effects of CA9-silencing in breast cancer cell lines. We found that CAIX-downregulation in hypoxia led to increased levels of let-7 (lethal-7) family members. Simultaneously with the increase of let-7 miRNAs in CAIX-suppressed cells, LIN28 protein levels decreased, along with downstream metabolic pathways: pyruvate dehydrogenase kinase 1 (PDK1) and phosphorylation of its substrate, pyruvate dehydrogenase (PDH) at Ser-232, causing attenuation of glycolysis. In addition to perturbed glycolysis, CAIX-knockouts, in correlation with decreased LIN28 (as CSC reprogramming factor), also exhibit reduction of the further CSC-associated markers NANOG (Homeobox protein NANOG) and ALDH1 (Aldehyde dehydrogenase isoform 1). Oppositely, overexpression of CAIX leads to the enhancement of LIN28, ALDH1, and NANOG. In conclusion, CAIX-driven regulation of the LIN28/let-7 axis augments glycolytic metabolism and enhances stem cell markers expression during CAIX-mediated adaptation to hypoxia and acidosis in carcinogenesis.
Keywords: proteiny vázající RNA; Glycolysis; MFC-7 buňky; Humans; carbonic anhydrase IX; Carbonic Anhydrase IX; MicroRNAs; hypoxie buňky; Female; glykolýza; karboanhydrasa IX; lidé; nádorové kmenové buňky; Neoplastic Stem Cells; Antigens, Neoplasm; LIN28/let-7 axis; antigeny nádorové; metabolism; Breast Neoplasms; ženské pohlaví; stanovení celkové genové exprese; Hydrogen-Ion Concentration; MCF-7 Cells; nádorové buněčné linie; nádory prsu; hypoxia; mikro RNA; Cellular Reprogramming; Cell Line, Tumor; Gene Expression Profiling; koncentrace vodíkových iontů; RNA-Binding Proteins; Cell Hypoxia; přeprogramování buněk